Port infrastructure efficiency: the Europe-Mediterranean case. (13th August 2009) - Liu, Qianwen; Medda, Francesca
The objective of this research is to estimate the infrastructure efficiency of individual ports, to investigate factors that influence efficiency and to shed light on infrastructure investment strategies. Thirty-two container ports in Europe-Mediterranean area have been assessed using stochastic frontier analysis. The result indicates the exogenous (environmental) factors, trading volume, which has a strong impact on port efficiency. Moreover, the infrastructure efficiency is improving over time, but the annual percentage change in output is slower than the technological change. This phenomenon is suggested due to over capacity, one of the most featured characteristics in container port industry. Different investment strategies to utilise and control over capacity in port management practice have been explored and suggested.